The Good in the Right : A Theory of Intuition and Intrinsic Value - Audi, Robert (Book collections on Project MUSE., 2004)
This book represents the most comprehensive account to date of an important but widely contested approach to ethics--intuitionism, the view that there is a plurality of moral principles, each of which we can know directly. Robert Audi casts intuitionism in a form that provides a major alternative to the more familiar ethical perspectives (utilitarian, Kantian, and Aristotelian) He introduces intuitionism in its historical context and clarifies--and improves and defends--W.D. Ross's influential formulation. Bringing Ross out from under the shadow of G.E. Moore, he puts a reconstructed version of Rossian intuitionism on the map as a full-scale, plausible contemporary theory. A major contribution of the book is its integration of Rossian intuitionism with Kantian ethics; this yields a view with advantages over other intuitionist theories (including Ross's) and over Kantian ethics taken alone. Audi proceeds to anchor Kantian intuitionism in a pluralistic theory of value, leading to an account of the perennially debated relation between the right and the good. Finally, he sets out the standards of conduct the theory affirms and shows how the theory can help guide concrete moral judgment. The Good in the Right is a self-contained original contribution, but readers interested in ethics or its history will find numerous connections with classical and contemporary literature. Written with clarity and concreteness, and with examples for every major point, it provides an ethical theory that is both intellectually cogent and plausible in application to moral problems.